2010
DOI: 10.1017/s0022112010000248
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulation of a flapping flag in a uniform flow

Abstract: A three-dimensional computational model is developed for simulating the flag motion in a uniform flow. The nonlinear dynamics of the coupled fluid–flag system after setting up of flapping is investigated by a series of numerical tests. At low Reynolds numbers, the flag flaps symmetrically about its centreline when gravity is excluded, and the bending in the spanwise direction is observed near the corners on the trailing edge. As the Reynolds number increases, the spanwise bending is flattened due to the decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(109 citation statements)
references
References 43 publications
16
93
0
Order By: Relevance
“…The rolling motion of the upper corner is also seen. These observations are consistent with the report in [10]. Figure 10 shows the time histories of the transverse displacements of points A in Figure 8 for Fr = 0.0.…”
Section: Three-dimensional Simulation Of a Flapping Flagsupporting
confidence: 91%
See 2 more Smart Citations
“…The rolling motion of the upper corner is also seen. These observations are consistent with the report in [10]. Figure 10 shows the time histories of the transverse displacements of points A in Figure 8 for Fr = 0.0.…”
Section: Three-dimensional Simulation Of a Flapping Flagsupporting
confidence: 91%
“…Figure 10 shows the time histories of the transverse displacements of points A in Figure 8 for Fr = 0.0. Both the result of present study and that of Huang & Sung [10] are plotted in the figure. An excellent agreement between the two results is clearly seen.…”
Section: Three-dimensional Simulation Of a Flapping Flagmentioning
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, there has been considerable research on the basic dynamics of flexible structures like flags, which can be bent, folded, twisted or waved in the air [19][20][21][22][23][24][25][26] . The first experimental study on fluttering behaviour was performed by Taneda 27 with a flag made of various fabrics and shapes, to find a variety of flapping modes (for example, nodeless, one-node, imperfect-node and two-node flutters).…”
mentioning
confidence: 99%
“…More recently, it was found that schooling fish can improve locomotion efficiency in side-by-side configuration [29,30]. Although most of the flexible bodies physically exist with a finite aspect ratio, only a few 3D simulations of an isolated flexible plate have been reported [31][32][33][34]. To our knowledge, the coupling motions and energy conversion performance of two side-by-side flexible plates in a 3D viscous flow have not been modeled and studied numerically yet.…”
Section: Introductionmentioning
confidence: 99%